The new Early Ordovician (Hunneberg Stage) graptolite genusParadelograptus (Kinnegraptidae), its phylogeny and biostratigraphy - Erdtmann, Bernd-D.; Maletz, Jörg; Gutiérrez-Marco, J. C. (Paläontologische Zeitschrift, 1987)
23 páginas, 10 figuras. [EN] Recent field investigations in the Sierra Morena (SW Spain), at the Hunneberg Mountain, Västergötland (Sweden) and in corresponding strata of the Cow Head Group (W. Newfoundland, Canada) as well as in the Lancefieldian (La2 to Bel) black shale bands of Victoria (Australia) have produced, inter alia, a diverse fauna of very delicate multibranched biradiate graptoloids (without bithecae), which possess “goniograptid” to “kinnegraptid” thecae and an adventitious number and arrangement of dichotomies (ranging from none to 6th and higher orders), reminiscent of the dendroid Adelograptinae Mu 1974. These characteristic forms are here assembled in the new genusParadelograptus, a genus which by virtue of its specific thecal morphology and its “adelograptoid” branching pattern is regarded as intermediate between the dendroid Adelograptinae Mu 1974 and the graptoloid family Kinnegraptidae Mu, 1974, into which this genus is here included. The following species are assigned toParadelograptus: P. onubensis n. sp. (type species),P. antiquus (Hall 1899),P. pritchardi (Hall 1899),P. smithi (Harris & Thomas 1938a),P. ramulosus (Harris & Thomas 1938a),P. sedecimus (Harris & Thomas (1938a),P. rarus (Harris & Thomas 1938a),P. problematicus (- “Clonograptus tenellus var. problematica”) Harris & Thomas 1938a,P. mosseboensis n. sp., andP. kinnegraptoides n. sp. A close relation toParadelograptus is also presumed for “Clonograptustenellus sensu lato” Cooper & Stewart 1979, “Tetragraptus”chapmani Keble & Harris 1934, “Tetragraptus”bulmani Thomas 1973, and “Tetragraptus”clarkefieldi Thomas & Keble in Harris & Thomas 1938b. Morphogenetic relations betweenParadelograptus and the dichograptinid (?) genusTrichograptus Nicholson 1876, the sigmagraptinid generaLaxograptus Cooper & Fortey 1982 andEtagraptus Ruedemann, 1904 as well as to the previously established kinnegraptid generaKinnegraptus Skoglund 1961,Prokinnegraptus Mu 1974, andWuninograptus Ni 1981 are also ...